2019
DOI: 10.1101/768291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hyaluronic acid particle hydrogels decrease cerebral atrophy and promote pro-reparative astrocyte/axonal infiltration in the core after ischemic stroke

Abstract: The death rate due to stroke is decreasing, resulting in more individuals living with stroke related disabilities. Following stroke, dying cells contribute to the large influx of highly reactive astrocytes and pro-inflammatory microglia that release cytokines and lead to a cytotoxic environment that causes further brain damage and prevents endogenous repair. Paradoxically, these same cells also activate pro-repair mechanisms that contribute to endogenous repair and brain plasticity. Here, we show that the dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…The observed reduction of monocytes in response to tetrazine‐norbornene crosslinked HA‐MAP scaffolds suggests an overall decrease in inflammation and is supported by our previous finding that HA‐MAP injection into the stroke cavity using an alternative chemistry for annealing upregulate Arginase‐1+ macrophages, which corresponds to a pro‐reparative, anti‐inflammatory phenotype. [ 20 ] Analysis of the astrocytic scar again revealed that similar to FXIIIa crosslinked HA‐MAP scaffolds, injection of Tet‐MAP into the stroke core visibly reduced astrocytic scar thickness (Figure 6G). Quantification of the scar thickness (Figure 6H) revealed statistical significance for thickness reduction with Tet‐MAP compared to sham groups (Figure 6I).…”
Section: Figurementioning
confidence: 99%
“…The observed reduction of monocytes in response to tetrazine‐norbornene crosslinked HA‐MAP scaffolds suggests an overall decrease in inflammation and is supported by our previous finding that HA‐MAP injection into the stroke cavity using an alternative chemistry for annealing upregulate Arginase‐1+ macrophages, which corresponds to a pro‐reparative, anti‐inflammatory phenotype. [ 20 ] Analysis of the astrocytic scar again revealed that similar to FXIIIa crosslinked HA‐MAP scaffolds, injection of Tet‐MAP into the stroke core visibly reduced astrocytic scar thickness (Figure 6G). Quantification of the scar thickness (Figure 6H) revealed statistical significance for thickness reduction with Tet‐MAP compared to sham groups (Figure 6I).…”
Section: Figurementioning
confidence: 99%
“…Remarkably, MAP gels have already demonstrated great promises in promoting functional tissue repair in wound healing and stroke with a reduced inflammatory response (e.g., reduced CD11b+ immune cell infiltration) (Griffin et al, 2015(Griffin et al, , 2020Sideris et al, 2016;Nih et al, 2017;Darling et al, 2020). Specifically, in stroke infarct areas filled with MAP gels, there is a much higher ratio of infiltrating pro-reparative arginase 1+ (Arg-1+) macrophage comparing to no treatment control (Sideris et al, 2019). Taken together, these results supported that MAP scaffold is not only appealing as a tool for elucidating the mechanotransduction pathways of macrophages, but also as a potent immunomodulatory platform for macrophagetargeting therapies.…”
Section: Macrophage-centered Immunomodulatory Biomaterials For Functimentioning
confidence: 99%
“…The chemical modifications further diversify the processing and fabrication techniques that may be employed to generate 3D HA scaffolds. Simple modifications to processing procedures enables the formation of HA hydrogels [ 74 ], granular hydrogels (microgels) [ 107 ], electrospun fibers [ 106 ], and composite HA-based materials [ 96 ]. Different forms of HA scaffolds have unique properties that provide different benefits to CNS regenerative medicine ( Figure 3 ).…”
Section: Therapeutic Relevance Of Ha-based Materials In the Cnsmentioning
confidence: 99%
“…Initial results with granular hydrogels for CNS applications indicate that they hold promise in modulating CNS inflammatory responses [ 24 ] and in controlled delivery of therapeutic molecules [ 128 ]. Sideris et al used granular hydrogels to promote repair after induced stroke in mice and found that the granular hydrogel promoted astrocyte infiltration into the stroke cavity while reducing glial scar formation post-injury [ 107 ]. Related experiments in rodent stroke models also demonstrated an increase in neural progenitor cell infiltration into the stroke cavity after treatment with granular hydrogels [ 24 ].…”
Section: Therapeutic Relevance Of Ha-based Materials In the Cnsmentioning
confidence: 99%
See 1 more Smart Citation